Awareness and approach in a sample of Community Pharmacists’ towards Patient Counseling in Thi-Qar/ Iraq and providing the appropriate solutions for the development of counseling - Nadem, Suha (University of Thi-Qar Journal of Science, 2023)
The main activity of community pharmacies throughout the world is directed with regard todispensing medication and patient care rather than compounding. Patients counseling has improved health-related outcomes in many acute and chronic conditions. The aim of this study is Assess the knowledge of community pharmacits about the counseling practice of patients in a sample of pharmacists in Thi-Qar/Iraq and Providing the appropriate means for developing the counseling and continuating education programs for community pharmacist. A cross-sectional study plan employing questionnaires was arranged based on previous studies and accomplished on a good specimen sample of sixty-one community pharmacists from Thi-Qar from separated areas of Thi-Qar participated in this survey. There were about (33%) of males and (67%) of females of respondents. The generality of pharmacists were giving advising to the patients and 65% of them drained 1-5 minutes for the purposes of deal with a prescription and provide counseling. Pharmacist concentrated on side effect, indication, duration, frequency and the dose of the drug during counseling in different proportions. Most pharmacists reported that patient response to counseling was mostly positive. One of the main strategies that was highlighted in overcoming the obstacles in patient counseling was providing special area in the pharmacy for counseling. Another important strategy was preparation of continuous pharmacist education programs that can assist in ameliorate the counseling practice furthermore.